Implementasi Intervensi Gizi Spesifik Pada Ibu Hamil dan Bayi di Desa Kalipang Kecamatan Grogol Kabupaten Kediri - Umianita Risca Wulandari; Dian Kumalasari (PROFESSIONAL HEALTH JOURNAL, 2024)
Background: Prolonged wasting and not receiving proper treatment will progress to stunting. One indicator of Medium Term Development is a reduction in stunting and wasting. Specific nutrition and nutrition sensitive intervention efforts were launched to overcome these nutritional problems. Assistance efforts are also needed to increase access for toddlers who are prone to nutritional problems. Objective: The purpose of this research is to analyze the implementation of specific nutritional interventions for pregnant women and babies in Kalipang Village, Grogol District, Kediri Regency. Method: This research is a qualitative analytical survey research with purposive sampling. The main informants were 20 people consisting of malnourished mothers of toddlers and stunted mothers of toddlers. Other informants involved were Puskesmas practitioners, Village Midwives, Village Officials and Posyandu cadres. The research was conducted in Kalipang Village, Grogol District, Kediri Regency. in January – March 2023. Data collection through in-depth interviews and document review, data analysis using direct interviews. Data analysis carried out data reduction, data display and drawing conclusions. Results: Implementation of specific interventions in Kalipang Village including pregnancy care (85%), administering blood supplement tablets (90%), implementing Early Breastfeeding Initiation (50%) and providing exclusive breastfeeding (20%). Conclusions and Suggestions: Most of the stunted and malnourished toddlers in Kalipang Village come from mothers of healthy reproductive age and KEK. Toddlers who have a history of LBW were born to mothers who were CED, had regular ANC, regularly took Fe tablets but did not provide exclusive breast milk. Research needs to be carried out regarding parental behavior in providing complementary foods to toddlers Keywords: Toddlers, Specific Nutritional Interventions